Critical Historical Thinking dalam Bingkai Peradaban: Analisis Integratif QS. Ghāfir [40]: 21 dan 82 Perspektif Tafsir Klasik-Kontemporer dan Kontribusinya Bagi Ummah - Sobari; Komarudin Sassi (Lembaga Intelektual Muda (LIM) Maluku, 2026)
This study aims to analyze the concept of critical historical thinking in the perspective of the Qur'an through a study of QS. Ghāfir [40]: 21 and 82. The study uses a library research method with a thematic-comparative approach that integrates classical and contemporary interpretations. The main data sources come from the works of the commentaries of al-Ṭabarī, Ibn Kathīr, Sayyid Quṭb, and al-Sha‘rāwī, while supporting data are obtained from relevant scientific literature. The analysis technique is carried out through the stages of data collection, reduction, comparative interpretation, and conceptual interpretation to find the construction of critical historical thinking in the Qur'anic perspective. The results of the study show that QS. Ghāfir [40]: 21 and 82 position history not merely as a narrative of the past, but as a means of empirical observation, analytical reflection, and transformation of civilization. Classical interpretations emphasize the sunatullah aspect and the destruction of previous peoples as moral lessons, while contemporary interpretations develop educational, social, and civilizational dimensions in understanding history. The key findings of this study demonstrate that Qur'anic critical historical thinking shapes critical, reflective, and progressive mindsets for Muslims in interpreting social and civilizational dynamics. The implications of this research emphasize the importance of integrating Qur'anic values ​​into history education and developing an awareness of Islamic civilization that is adaptive to the challenges of modernity.